Epidemiological characteristics: traumatic cervical spinal cord injury in Wuhan-China - Ruba Altahla; Jamal Alshorman; Xu Tao (Academia Medicine)
Traumatic cervical spinal cord injury (TCSCI) is a severe injury that can cause permanent disability, affect sensory and motor function, and lead to dysfunctions in other systems. This study aimed to characterize the current epidemiological profile of TCSCI in Wuhan, Hubei, China. The records of 340 patients from two hospitals between January 2019 and August 2023 were reviewed. A total of 273 patients with TCSCI were included, and 67 were excluded. Complete clinical records for this period were accessible from all databases. Patient age, gender, cause of injury, neurological level, American Spinal Injury Association (ASIA) grades, and associated trauma were all factors we looked for in the patient records. This study had 273 patients with TCSCI. The mean age was 47.2 ± 14.3 years (ranging from 15 to 85 years), and the male-to-female ratio was 2:1. The primary cause of TCSCI was falls, accounting for 58.8% of cases, followed by traffic accidents, which contributed to 35.1% of the injuries. Among the patients, the most commonly affected spinal level was C4, representing 52%. The ASIA grade B classification was also the most prevalent, observed in 29.6% of the patients. The epidemiological characteristics of TCSCI in Wuhan are distinct, highlighting the need for preventive measures targeted at middle-aged individuals. There is a higher incidence of TCSCI in males than females, the most frequently affected level is C4, and ASIA grade B represents the highest prevalence. These findings illustrate the importance of preventive measures for the specific traits of the TCSCI patient population.